Mosaici funerari tardoantichi in Italia : repertorio e analisi - Quattrocchi, Luigi, (Archaeopress Publishing Ltd, 2018)
The potential of tomb mosaics as an academic resource has often been underestimated and consequently they have only been partially analysed not only in Italy but also throughout the Western Mediterranean. This work is intended to shed a new light on these finds, which are often incomplete, lost, or little studied.